New optical coherence tomography grading system for macula-off rhegmatogenous retinal detachment: how off is off?. Issue 1 (8th March 2021) - Boden, Karl Thomas; Januschowski, Kai; Szurman, Peter; Seuthe, Anna-Maria; Rickmann, Annekatrin; Seitz, Berthold; Alsharairi, Mohammad; Leers, Stephan; Wakili, Philip
Abstract : Background/Aims: The classification of retinal detachment is currently still based on many objective criteria such as duration of symptoms and funduscopic macular status, which leaves some important questions unanswered. The most important factor is the macular status, which is determined using direct or indirect ophthalmoscopy. Optical coherence tomography (OCT) has become a standard tool in clinical practice and enables detecting the exact extent of subretinal fluid in macula-off/on retinal detachment. We introduce a new and simple OCT-based grading system for macular detachment to provide a basis for further investigations to determine the optimal timing for surgery. Methods: We retrospectively included 155 patients who were treated for retinal detachment. We defined the extent of the macular detachment in six stages based on the Early Treatment Diabetic Retinopathy Study (ETDRS) grid of the OCT scan. The outermost ring of the ETDRS grid was defined as zone 1, the middle ring as zone 2 and the inner ring as zone 3. Only zone 3 differed in the retinal detachment height grades (grade a <250 µm vs grade b >250 µm). Retinal detachment heights that could not be measured were considered grade 4 (ungradable) detachments. Results: Forty-seven patients had no macular involvement (grade 0). Regarding macular detachment, 14 patients had grade 1, 20 had grade 2, 9 had grade 3a, 29 had grade 3b and 36 had grade 4. Conclusion: The newly developed OCT grading system for macular involvement following retinal detachment is a crucial tool to objectively classify a retinal detachment in order to be able to make better statements in the future, like for defining the optimal time for surgical intervention. A secondary benefit of this grading system would be that it improves predicting postoperative visual acuity.